An interdependent infrastructure asset management framework for high-density cities. Issue 3 (29th September 2021) - Zhong, Chen; Ng, S. Thomas; Skitmore, Martin
Abstract : Infrastructure facilities, namely highways, drinking water networks, sewerage systems, gas pipelines and telecommunication networks are crucial to the daily operation and continuous development of high-density cities. However, managing these infrastructure assets is not an easy task not only because the co-existence of various infrastructure facilities is in confined spaces, but also due to the interdependency and hence the possible cascading effects brought by the failure of one infrastructure asset to the other adjacent facilities. The ability to share and exchange information among various government departments and utility companies should greatly improve the efficiency and cost-effectiveness of infrastructure asset management (IAM). This paper examines the processes, stakeholders and independent relationships involved in IAM through two case infrastructure studies of Hong Kong. Flow diagrams are used to illustrate the process and stakeholders involved while system dynamics modelling is performed to simulate the interactions. Generic causal models are then developed to help improve the IAM process in high-density cities. The proposed interdependent IAM framework should help improve our understanding on the bottlenecks and pave way for the development of pragmatic policies and practices for smart and resilient high-density cities.